Gender and masculinities: histories, texts and practices in India and Srilanka - Doron, Assa (ed.); Broom, Alex (ed.) (New Delhi, 2014)
Routledge india, New Delhi, 2013. Hardcover. Book Condition: New. 203pp. Masculinities, and their discontents, are an understudied and often misrepresented facet of gender relations and cultural dynamics. This volume unravels the complex ideas, practices and concepts revolving around gender structures and masculinities in India and Sri Lanka. Readership:ÿScholars and students of gender studies, history, anthropology, sociology, politics and popular culture.
Keywords: Men; India; Sri Lanka